The Pricing Policy for Hotel Services in Poland in the Light of Surveys - Aleksandra BANASZKIEWICZ; Ewa MAKOWSKA (Communications of International Proceedings, 2020)
The main purpose of the article is to present the results of the survey on pricing strategies for hotel services in a selected region of Poland, namely the Kujawsko-Pomorskie and Pomorskie provinces. The survey was carried out twice, with a five-year interval, i.e. in 2014 and 2019. This enabled the comparison of the obtained data. The survey was aimed at verifying the thesis that determining the prices of hotel rooms is made on the basis of certain factors, mainly such as: the wealth of the society and its tourist awareness, the attractiveness of the region, the state of development of both domestic and international tourism, as well as the needs of business in terms of the need for hotel services.
Keywords: The Pricing Policy For Hotel Services; Tourism; Hotel Industry.